Heat Development in the Pulp Chamber During Curing Process of Resin-Based Composite Using Multi-Wave LED Light Curing Unit - Nilsen BW; Mouhat M; Haukland T; Örtengren UT; Mercer JB (Dove Medical Press, 2020)
Bo Wold Nilsen,1,* Mathieu Mouhat,1,* Torbjørn Haukland,1 Ulf Thore Örtengren,1,2 James B Mercer3 1Department of Clinical Dentistry, UiT - the Arctic University of Norway, Tromsø, Norway; 2Department of Cariology, Institute of Odontology/Sahlgrenska Academy, Gothenburg, Sweden; 3Department of Medical Biology, UiT - the Arctic University of Norway, Tromsø, Norway*These authors contributed equally to this workCorrespondence: Mathieu Mouhat Email mathieu.mouhat@uit.noObjective: The study aimed to investigate factors contributing to heat development during light curing of a flowable bulk-fill resin-based composite (SDRTM, Lot # 602000876, Dentsply Sirona, Konstanz, Germany) (RBC).Materials and Methods: Temperatures were measured with calibrated thermocouples. A multi-wave light-emitting diode (LED) light curing unit (LCU) was used (Ivoclar Vivadent, Schaan, Lichtenstein). In all experiments, the RBC was first cured (cured) for 30 s and, after 5 min of recovery time, received a second LCU irradiation (post-cured) for 30 s. The exothermic reaction was measured by calculating the Δ temperature between cured and post-cured RBC. In a cylinder-shaped polymer mold, temperature was recorded inside of RBC during curing (part 1) and light transmission through RBC during curing was investigated (part 2). Pulpal temperatures were assessed in an extracted third molar during light curing (part 3). Data were statistically analyzed using one-way ANOVA (α=0.05).Results: Increased thickness of RBC led to decreased pulp chamber temperatures. Inside RBC, there was a large variation in heat development between the cured and post-cured groups (p< 0.05). The cured group absorbed more LCU irradiation than the post-cured group.Conclusion: The irradiance of the LCU seemed to be a more important factor than exothermic reaction of RBCs for pulp chamber heat development. Flowable bulk-fill RBCs can act as a pulpal insulator against LCU irradiation, despite their exothermic curing reaction.Keywords: dentistry, composite resins, LED dental curing light, pulp chamber, temperature